2022
DOI: 10.3390/ijerph20010734
|View full text |Cite
|
Sign up to set email alerts
|

Measuring the Non-Linear Relationship between Three-Dimensional Built Environment and Urban Vitality Based on a Random Forest Model

Abstract: Urban vitality is a major indicator used for evaluating the sustainability and attractiveness of an urban environment. Global experience indicates that urban vitality can be stimulated through a reasonable urban design. However, it remains incompletely understood in the literature which building-related indicators can substantially affect urban vitality in Asian countries. To give an insight into this question, our study took a step forward by focusing specifically on the influence of the three-dimensional bui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 80 publications
0
13
0
Order By: Relevance
“…Due to two random variables, RF is insensitive to noisy data and can avoid overfitting. The use of RF is widespread due to its good performance [ 32 ], and support vector machine (SVM) is commonly used, since it is suitable for small samples with poor information [ 33 ]. By assigning weights to the training errors in WLSSVM, the learning ability of the model is improved and noise in the training samples is effectively reduced.…”
Section: Methodsmentioning
confidence: 99%
“…Due to two random variables, RF is insensitive to noisy data and can avoid overfitting. The use of RF is widespread due to its good performance [ 32 ], and support vector machine (SVM) is commonly used, since it is suitable for small samples with poor information [ 33 ]. By assigning weights to the training errors in WLSSVM, the learning ability of the model is improved and noise in the training samples is effectively reduced.…”
Section: Methodsmentioning
confidence: 99%
“…A commercial cluster is an urban functional area that integrates commodity purchase, marketing display, entertainment experience, commercial offices, and regional logistics, rendering it the fifth generation of merchandising markets in China. Studies have shown that improving the number of visits to commercial stores, increasing the assortment of businesses, and balancing the homogeneity of commercial vitality can contribute to the effective operation of a commercial cluster [1][2][3]. The commercial vitality of a mature commercial cluster needs to be well-balanced, and store visits need to be evenly distributed among the commercial clusters [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…The aim of this research was to explain the spatiotemporal variations in, and pattern of, traffic flow, to control the error rate, and to improve the accuracy of prediction results through empirical studies [13][14][15]. (3) Using the detection results of the traffic flow, including information on the traffic flow, vehicle travel speed, and urban spatial distribution, researchers aimed to study the problem of urban carbon emissions, urban traffic, and urban infrastructure services and facilities [16][17][18]. The abovementioned studies on traffic flow are limited in the following ways: (1) They require the completeness of the original data, making it difficult to obtain traffic information for a wide range of areas in locations with low data openness, resulting in prediction errors.…”
Section: Introductionmentioning
confidence: 99%
“…The term "urban vitality" was widely accepted to describe the quality, sustainability, attractiveness of spaces that attract people for different types of activities to produce diverse city life [1,2]. Higher urban vitality usually means stronger attraction to people, the ability to support demands of different people, and the potentiality of development [3,4]. Improving the urban vitality is significant to the urban development and human lives, and the evaluation of current situation is the basic work [2,5].…”
Section: Introductionmentioning
confidence: 99%
“…With the help of open data platform, web crawler, and network API, etc., open-access geographic big data can be easily acquired. Different from the standard raster data format of remote sensing data, the spatial quantization of geographic big data within cities still needs specific analysis for data types and research basic unit [4].…”
Section: Introductionmentioning
confidence: 99%